Sistem Terintegrasi untuk Perencanaan dan Pengendalian Pembangunan Wilayah Berbasis Kampung - Zaidir Zaidir; Indra Listiawan (JISKA (Jurnal Informatika Sunan Kalijaga), 2020)
Development planning in the village begins with the Development Planning Conference. The government considers the need for solutions in solving development problems up to the village and village level so that on November 7, 2018 a Mayor Regulation number 72 of 2018 concerning the formation of village administrators is issued so that development is no longer based on RT-RW but based on village. The many functions of village administrators need an appropriate system for processing data. Manually processing data has weaknesses, especially in planning and controlling budget. The purpose of this study is to produce an integrated system for planning and controlling village-based area development. The research method used consists of library research, data collection and system development of the Waterfall method (system analysis, system design, system implementation and system testing). The results of this study are a system that is capable of processing data from budget proposals to reporting and can provide varied information for village administrators, LPMK and Kelurahan.